Participatory design: lessons and directions for responsible research and innovation - Ten Holter, C (Taylor and Francis, 2022)
This review compares and discusses the literature and practice of participatory design (PD) and responsible research and innovation (RRI) to discover commonalities and contrast their approaches to similar challenges found in such ‘participatory’ methods. It seeks to gain insights from the older practice of PD and attempts to discover whether there are lessons that RRI could usefully draw on to address its own challenges. The paper suggests that PD’s understandings of the politics and power dynamics surrounding inclusive methods; its democratisation imperative; and its nascent development of project documentation may offer useful considerations for RRI. The paper concludes with some concrete suggestions for RRI as it continues to develop and be operationalised.